Health-related quality of life in patients with microsatellite instability-high or mismatch repair deficient metastatic colorectal cancer treated with first-line pembrolizumab versus chemotherapy (KEYNOTE-177): an open-label, randomised, phase 3 trial. Issue 5 (May 2021) - Andre, Thierry; Amonkar, Mayur; Norquist, Josephine M; Shiu, Kai-Keen; Kim, Tae Won; Jensen, Benny Vittrup; Jensen, Lars Henrik; Punt, Cornelis J A; Smith, Denis; Garcia-Carbonero, Rocio; Sevilla, Isabel; De La Fouchardiere, Christelle; et al.
Summary: Background: In the KEYNOTE-177 study, pembrolizumab monotherapy provided statistically significant and clinically meaningful improvements in progression-free survival versus chemotherapy as first-line treatment in patients with microsatellite instability-high or mismatch repair-deficient metastatic colorectal cancer. To further support the efficacy and safety findings of the KEYNOTE-177 study, results of the health-related quality of life (HRQOL) analyses are reported here. Methods: KEYNOTE-177 is an open-label, randomised, phase 3 trial being done at 192 cancer centres in 23 countries, in patients aged 18 years and older with microsatellite instability-high or mismatch repair-deficient metastatic colorectal cancer, with an Eastern Cooperative Oncology Group performance status of 0 or 1, and who had not received previous systemic therapy for metastatic disease. Eligible patients were randomly assigned (1:1) centrally by use of interactive voice response or integrated web response technology to receive pembrolizumab 200 mg intravenously every 3 weeks or investigator's choice chemotherapy (mFOLFOX6 [leucovorin, fluorouracil, and oxaliplatin] or FOLFIRI [leucovorin, fluorouracil, and irinotecan] intravenously every 2 weeks with or without intravenous bevacizumab or cetuximab). Patients and investigators were not masked to treatment assignment. The primary endpoints were progression-free survival (previously reported) and overall survival (data to be reported at the time of the final analysis). HRQOL outcomes were evaluated as prespecified exploratory endpoints. The analysis population comprised all randomly assigned patients who received at least one dose of study treatment and completed at least one HRQOL assessment. HRQOL outcomes were mean change from baseline to prespecified week 18 in European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30) and EORTC Quality of Life Questionnaire-Colorectal 29 (EORTC QLQ-CR29) scale and item scores, and in the EuroQoL 5 Dimensions 3 Levels (EQ-5D-3L) visual analogue scale and health utility scores; the proportion of patients with improved, stable, or deteriorated scores from baseline to prespecified week 18 in EORTC QLQ-C30 scales and items; and time to deterioration in EORTC QLQ-C30 global health status/quality of life (GHS/QOL), physical functioning, social functioning, and fatigue scores and EORTC QLQ-CR29 urinary incontinence scores. The threshold for a small and clinically meaningful mean difference in EORTC QLQ-C30 score was 5–8 points. This study is registered with ClinicalTrials.gov, NCT02563002 and is ongoing; recruitment is closed. Findings: Between Feb 11, 2016, and Feb 19, 2018, 307 patients were enrolled and randomly assigned to receive pembrolizumab (n=153) or chemotherapy (n=154). The HRQOL analysis population comprised 294 patients (152 receiving pembrolizumab and 142 receiving chemotherapy). As of Feb 19, 2020, median time from randomisation to data cutoff was 32·4 months (IQR 27·7–37·8). Least squares mean (LSM) change from baseline to prespecified week 18 showed a clinically meaningful improvement in EORTC QLQ-C30 GHS/QOL scores with pembrolizumab versus chemotherapy (between-group LSM difference 8·96 [95% CI 4·24–13·69]; two-sided nominal p=0·0002). Median time to deterioration was longer with pembrolizumab versus chemotherapy for GHS/QOL (hazard ratio 0·61 [95% CI 0·38–0·98]; one-sided nominal p=0·019), physical functioning (0·50 [95% CI 0·32–0·81]; one-sided nominal p=0·0016), social functioning (0·53 [95% CI 0·32–0·87]; one-sided nominal p=0·0050), and fatigue scores (0·48 [95% CI 0·33–0·69]; one-sided nominal p<0·0001). Interpretation: Pembrolizumab monotherapy led to clinically meaningful improvements in HRQOL compared with chemotherapy in patients with previously untreated microsatellite instability-high or mismatch repair-deficient metastatic colorectal cancer. These data, along with the previously reported clinical benefits, support pembrolizumab as a first-line treatment option for this population. Funding: Merck Sharp & Dohme, a subsidiary of Merck & Co, Kenilworth, NJ, USA.